THE IMPROVEMENT OF ENERGY EFFICIENCY IN AVIATION AND AIR CARGO PUBLIC FACILITIES IN NIGERIA: A CALL FOR POLICY AND SUPPORTIVE REGULATORY FRAMEWORKS - Abdullahi Imam MUSA; Taiwo Ezekiel ADEBAKIN; Salisu Ojonemi PAUL; Chekwume Anthony OKOLIE (Scientific Journal of Silesian University of Technology. Series Transport)
This study explores the assessment of design strategies to improve energy efficiency in aviation facilities. The energy that Nigerian civil aviation sector facilities consume is substantial, with considerable implications for operational costs and environmental impact. This research investigates energy consumption patterns, evaluates the effectiveness of current design strategies and technologies, and identifies specific challenges hindering optimal energy efficiency. The study employs secondary data to study various aviation facilities. Findings reveal that while advanced building materials, passive design principles, and energy-efficient technologies have been adopted to some extent, significant variability exists in their implementation. The paper pinpointed major identifiable challenges that were not far-fetched from lack of awareness to high initial costs, and insufficient regulatory frameworks. The impact of these design strategies on indoor air quality and thermal comfort is also analyzed, highlighting improvements in occupant comfort and satisfaction in facilities with robust energy-efficient practices. The study concludes with recommendations for enhancing regulatory frameworks, increasing awareness and training, promoting financial incentives, and adopting integrated design approaches. These insights aim to guide industry stakeholders, policymakers, and researchers in advancing energy efficiency and sustainability in aviation facilities.